Implementation of guided inquiry model to improve students science literacy on earth and their satellites material - Kirani Nur Cahyani; Dhita Ayu Permata Sari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to describe the results of implementing the guided inquiry model to scientific literacy in the Earth and Satellite material. The type of research used is descriptive through the design pretest-posttest with one group. The subjects in this study were 36 students in class VII-A at Junior High School 1 Wonoayu Sidoarjo, even semester of the 2022/2023 academic year. Data collection techniques using observation, tests, and questionnaires. The research instruments included learning implementation observation sheets, scientific literacy tests, and student response questionnaire sheets. The test results were analyzed using paired t-test and counting effect size. The results showed that implementing learning using the guided inquiry model on the Earth and Satellite material obtained very well-implemented criteria with mode 4. The student's scientific literacy skills had increased, as evidenced by the paired t-test results of 0.000 and the calculation effect size of 1.823. Students' scientific literacy level after most learning is at level 4. The most significant increase in scientific literacy competence is in the indicator of explaining phenomena scientifically at 27.08, then the indicator of interpreting data and evidence scientifically at 23.15, and the indicator of designing and evaluating scientific investigations at 6.29. The learning process using the guided inquiry model on Earth and its satellite material was also very well received by students, with 66.67% of statements in mode 4. Based on the description above, implementing the guided inquiry model can increase students' scientific literacy in the Earth and Satellite material.